I must say my life as a humble comedy legend - Short, Martin 1945- (HarperCollins, 2014)
The Emmy Award and Tony Award-winning actor and comic shares stories from his life that recount his early years with Saturday Night Live, the development of his numerous characters, his family life and his celebrity friendships
ON ORD 10/28/14 Nonfiction
An ed-ucation -- Humble celebrity me -- Marty with parents -- Interlude: a moment with Irving Cohen -- Marty without parents -- In which I find Jesus -- Nancy's boy -- Interlude: a moment with Ed Grimley -- The nine categories -- Interlude: a moment withJackie Rogers Jr. -- Workplace nirvana at SCTV -- Interlude: a moment with Lawrence Orbach -- Fast times at 30 rock -- Eighties-hot -- Marty throws a party just to sing -- Interlude: a moment with Franck -- When life hands you lemons, put on a fat suit and squash them between your thighs -- Interlude: a moment with Jiminy Glick -- Love, loss, and bumpkiss -- Kathie Lee wasn't wrong -- September of my years-but an unusually temperate September
Keywords: Short, Martin / 1950-; Comedians / United States / Biography; Actors / United States / Biography; USA; Biografie